On the Use of the Disability-Adjusted Life Year (DALY) Estimator as a Metric to Optimally Manage ICE Emissions - Antonio Rossetti; Nicola Andretta; Alarico Macor (Energies, 2022)
We propose a new management strategy for engines equipped with automatic transmissions based on the damage to human health caused by emissions. The damage to human health is quantified by the years of life lost in a population due to disability or early death caused by exposure to pollutants. Various engine emissions share a common factor: damage to human health. Our strategy aims to keep engines running along the line of minimum damage instead of focusing on minimal fuel consumption. We applied the minimum damage strategy to the powertrain of a light vehicle to evaluate its effectiveness. In this work, we discuss this strategy’s effects on continuous variable transmission and seven gears automatic transmission and compare the classic minimum fuel consumption strategy to the minimum damage strategy. The latter results in a 50% reduction in damage compared with the minimum consumption strategy at the expense of an 8% increase in fuel consumption.